Integrated sustainable household solid waste management using solid waste minimisation approach in Shah Alam, Selangor - Ali, Nor Eeda (2017)
Good solid waste management has emerged as a vital element in creating cities that offer a healthy and comfortable environment for living. Municipal solid waste poses an environmental problem particularly in cities that have experienced rapid growth. Solid waste minimisation is a way of reducing the amount of solid waste generated by households. This study investigates solid waste minimisation practice among urban households in Shah Alam, Selangor and provides insight on the roles of various stakeholders involved in waste management. The study also examines the influence of households socio-demographic characteristics on psychological factors, knowledge and behaviour affecting solid waste minimisation and the quantity and composition of solid waste generated monthly per household. The study employed both inferential and descriptive analyses. Findings revealed that knowledge on solid waste minimisation has statistically significant associations with 5 socio-demographic characteristics, namely age [F(4, 295) = 2.36, p = 0.05]; race [F(2, 297) = 2.84, p = 0.05]; marital status [F(2, 297) = 2.83, p = 0.05]; monthly income [F(3, 296) = 2.86, p = 0.037] and home ownership [F(2, 297) = 5.01, p = 0.007]. Results also showed that behaviour towards waste minimisation is significantly associated with marital status [F(2, 297) = 3.51, p = 0.031], gender [F = 7.328, p = 0.00] and home ownership [F(2, 295) = 7.57, p = 0.001]. In terms of solid waste generation, the results showed that 0.46 kg of waste generated per capita per day with a composition of 45.51% recyclable materials, 33.98% food and 20.51% non-recyclable materials. The study found that the various stakeholders (waste contractor, household, junkshop, local authority, Non-Government Organisations (NGOs), Community Based Organisations (CBOs), educational institution, scavenger) act independently and there was no proper coordination existed among them in solid waste management. Therefore, local authorities should work on the collaboration with other stakeholders in providing systematic education to enhance solid waste minimisation. Based on the results of the study, a conceptual framework of Integrated Sustainable Household Solid Waste Management (ISHWM) was developed taking into account the current regulations.